2018
DOI: 10.14814/phy2.13651
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and exercise training-induced increase in autophagy markers in human skeletal muscle

Abstract: Moderately trained male subjects (mean age 25 years; range 19–33 years) completed an 8‐week exercise training intervention consisting of continuous moderate cycling at 157 ± 20 W for 60 min (MOD; n = 6) or continuous moderate cycling (157 ± 20 W) interspersed by 30‐sec sprints (473 ± 79 W) every 10 min (SPRINT; n = 6) 3 days per week. Sprints were followed by 3:24 min at 102 ± 17 W to match the total work between protocols. A muscle biopsy was obtained before, immediately and 2 h after the first training sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 27 publications
7
69
5
1
Order By: Relevance
“…On the other hand, the increase in p62 observed following the training period in both the hypertensive and the normotensive group suggests that the capacity for autophagy regulation increased with exercise training independent of hypertension. Overall, the present findings are in contrast to the unaltered levels of LC3‐II and p62 documented in either healthy young or elderly men following an exercise training period, with such discrepancies possibly related to the different characteristics of the populations and the exercise training interventions employed. It should be noted that even though LC3 and p62 have been widely used as markers of autophagy, they are indicators of the rate of lysosome formation, but not degradation, which would provide a more specific measure of the autophagic flux .…”
Section: Discussioncontrasting
confidence: 98%
“…On the other hand, the increase in p62 observed following the training period in both the hypertensive and the normotensive group suggests that the capacity for autophagy regulation increased with exercise training independent of hypertension. Overall, the present findings are in contrast to the unaltered levels of LC3‐II and p62 documented in either healthy young or elderly men following an exercise training period, with such discrepancies possibly related to the different characteristics of the populations and the exercise training interventions employed. It should be noted that even though LC3 and p62 have been widely used as markers of autophagy, they are indicators of the rate of lysosome formation, but not degradation, which would provide a more specific measure of the autophagic flux .…”
Section: Discussioncontrasting
confidence: 98%
“…Physical exercise has been identified as an inducer of autophagy (Halling and Pilegaard, 2017;Martin-Rincon et al, 2018). Exercise was reported to induce autophagy in several organs such as cardiac tissue, skeletal muscle, liver, pancreas, hippocampus, and adipose tissue (Brandt et al, 2018;Li et al, 2018b). Induction of skeletal and cardiac muscle autophagy during endurance training triggers beneficial adaptive changes in mitochondrial metabolism and is associated with enhanced physical fitness (Lira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exercise training is known to induce long-term biochemical and morphological adaptations. These alterations include enhanced mitochondrial content brought upon by changes in both mitochondrial biogenesis and mitophagy [3,43]. Ju et al [24] and Lira et al [34] have found an increase in autophagy and mitophagy markers with exercise training.…”
Section: Effect Of Chronic Exercise On Mitophagymentioning
confidence: 99%
“…These increases were likely due to transient Ca 2+ fluxes and subsequent calcineurin activation, since inhibition of calcineurin prevented TFEB translocation to the nucleus. Another mechanism that may be involved in the contractile activity induced increase in AMPK phosphorylation, which can negatively regulate mTORC1 function [3,23]. This inactivation of mTORC1 may reduce TFEB phosphorylation, thereby promoting its nuclear localization, an effect that was not apparent in PGC-1α KO mice, suggesting an additional role for PGC-1α as an enhancer of TFEB-mediated autophagic induction [12].…”
Section: Effect Of Acute Endurance Exercise On Mitophagymentioning
confidence: 99%